The KMOS Galaxy Clusters Project. Issue Volume 10:Issue S311(2014) (10th April 2015) - Davies, Roger L.; Beifiori, A.; Bender, R.; Cappellari, M.; Chan, J.; Houghton, R.; Mendel, T.; Saglia, R.; Sharples, R.; Stott, J.; Smith, R.; Wilman, D.
Abstract: KMOS is a cryogenic infrared spectrograph fed by twentyfour deployable integral field units that patrol a 7.2 arcminute diameter field of view at the Nasmyth focus of the ESO VLT. It is well suited to the study of galaxy clusters at 1 < z < 2 where the well understood features in the restframe V-band are shifted into the KMOS spectral bands. Coupled with HST imagining, KMOS offers a window on the critical epoch for galaxy evolution, 7-10 Gyrs ago, when the key properties of cluster galaxies were established. We aim to investigate the size, mass, morphology and star formation history of galaxies in the clusters. Here we describe the instrument, discuss the status of the observations and report some preliminary results.